2016
DOI: 10.1007/s10995-016-2075-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Internet Use by Pregnant Women, and Reliability of Pregnancy-Related Searches

Abstract: Objective To assess patterns of e-health use in pregnancy in an underserved racially diverse inner-city population, and to assess the accuracy of pregnancy-related information obtained from the Internet. Methods A cross sectional study of 503 pregnant/postpartum women belonging to an underserved racially diverse inner-city population who completed a survey regarding e-health use. To assess accuracy, four independent expert-reviewers rated the first 10 webpages on Google searches for each of five questions base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 12 publications
4
52
1
3
Order By: Relevance
“…17 With the dramatic rise of accessibility of the internet and its widespread use by the general Australian population, 18,19 this trend is not surprising. The accuracy of online information targeted to pregnant women has been evaluated by some authors, [20][21][22][23] however regularly monitoring is required due to the rapid expansion of online sites, and the risk that nutrition misinformation may pose to women if they follow non-evidence-based advice. 24 The aim of the present study was to (a) identify where women source their nutrition information during pregnancy and whether this has changed over time across multiple surveys and (b) assess the accuracy of nutrition information for pregnancy that is available online.…”
Section: Introductionmentioning
confidence: 99%
“…17 With the dramatic rise of accessibility of the internet and its widespread use by the general Australian population, 18,19 this trend is not surprising. The accuracy of online information targeted to pregnant women has been evaluated by some authors, [20][21][22][23] however regularly monitoring is required due to the rapid expansion of online sites, and the risk that nutrition misinformation may pose to women if they follow non-evidence-based advice. 24 The aim of the present study was to (a) identify where women source their nutrition information during pregnancy and whether this has changed over time across multiple surveys and (b) assess the accuracy of nutrition information for pregnancy that is available online.…”
Section: Introductionmentioning
confidence: 99%
“…Today the internet is an important source of information for individuals who are concerned about their health . Studies have revealed that pregnant women use the internet quite often to access information related to pregnancy and to make decisions regarding their health . In the current study, most of the pregnant women stated that their leading source of information related to pregnancy was the “internet,” and about half of them searched the internet about pregnancy‐related issues from the moment they were diagnosed as pregnant.…”
Section: Discussionmentioning
confidence: 69%
“…A study determined that more than half of the pregnant women thought that the information they obtained from the internet was valid and reliable . In another study conducted on the participants’ satisfaction with e‐health pages, 89.8% of the women regarded these pages as practical, 87% as appropriate, and 83.7% as useful . In contrast to these findings, in Kim and Kim (2009) study, 39.9% of the participants thought that health‐related information obtained from the internet was “wrong” and 42.7% believed that this information “was not appropriate for the health status of the patients.” Many women want to get the latest information to make them feel safer in pregnancy and expect health professionals to offer them a reliable website .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations